Pengembangan Media Edukasi Hidrologi Tiga Dimensi (HIDRA 3D) Berbasis Augmented Reality Sebagai Alat Peraga Untuk Pembelajaran IPAS Di Kelas V MI Salafiyah Syafi’iyah Bangsalsari Jember Tahun Pelajaran 2025/2026 - Safinatun Najah; Muhammad Junaidi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study was motivated by the low level of students' understanding and learning motivation in learning the water cycle material in Science and Social Studies (IPAS) for fifth-grade students at MI Salafiyah Syafi'iyah Bangsalsari Jember. To address this issue, a Three-Dimensional Hydrology Educational Media (HIDRA 3D) based on Augmented Reality was developed as an interactive and innovative learning aid. This study aimed to determine the development process, validity, practicality, and effectiveness of the HIDRA 3D media.The research employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through observation, interviews, questionnaires, documentation, and pretest-posttest tests.The results showed that the HIDRA 3D media based on Augmented Reality was highly valid, with an average validation score of 93.33% from material, media, and learning experts. The practicality test obtained an average score of 87.93%, indicating that the media was highly practical. The effectiveness test demonstrated an improvement in students' learning outcomes, with the average pretest score increasing from 61.30 to 85.21 on the posttest and an N-Gain score of 0.61 in the moderate category. Therefore, HIDRA 3D media is considered highly valid, practical, and effective for supporting IPAS learning on the water cycle material.